Measuring the impact of POWER! programme - Sabri, Mohamad Fazli; Abdullah, Siti Farra Zillah (Scholars Middle East Publishers, 2016)
Despite the vast research in financial literacy and financial education, little is known about the effectiveness of the education programme that was conducted to increase the financial literacy among Malaysian. The high number of bankruptcy as the highest bankruptcy case was related to hire purchase loans and personal loans are among the crucial financial issues in Malaysia. Hence, this study was conducted to investigate the financial literacy, attitude and practices of those who attended POWER! programme and not attended. Data were obtained through on-line survey (n=677) and during Minggu Amanah Saham Malaysia. The findings include that after 6 months attended POWER! programme the participants have a higher financial knowledge. In addition, those who attended POWER! programme had positive attitude towards financial matters although mix result was observed. On the other hand, the control group have better in basic financial behaviour. Consequently, interview should be conducted to gain more understanding on the impact of POWER! programme, a detailed module on specific personal finance need to be developed and further study on financial attitude and behaviour is needed.